2020
DOI: 10.1155/2020/1453893
|View full text |Cite
|
Sign up to set email alerts
|

Combined Heat and Mass Transfer of Fluid Flowing through Horizontal Channel by Turbulent Forced Convection

Abstract: In the present paper, we report a numerical study of dynamic and thermal behavior of the incompressible turbulent air flow by forced convection in a two-dimensional horizontal channel. This one contains the complicated form of the deflector which has been studied by varying the inclination angle from φ = 40°, φ = 55° to φ = 65°. The baffles are mounted on lower and upper walls of the channel. The walls are maintained at a constant temperature (375 K), the inlet velocity of air is Uint = 7.8 m/s, and the Reynol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The channel and rib geometry is indicated in Figure 6. Salhi et al [14] made a numerical investigation study to examine heat transfer performance affection the inclination angle of the involved baffles in a two-dimensional horizontal channel. The baffles are mounted on lower and upper walls of the channel and inclination angles are 40°, 55° and 65°.…”
Section: Solid Ribs Blocks and Bafflesmentioning
confidence: 99%
“…The channel and rib geometry is indicated in Figure 6. Salhi et al [14] made a numerical investigation study to examine heat transfer performance affection the inclination angle of the involved baffles in a two-dimensional horizontal channel. The baffles are mounted on lower and upper walls of the channel and inclination angles are 40°, 55° and 65°.…”
Section: Solid Ribs Blocks and Bafflesmentioning
confidence: 99%
“…analyzed the flow structure and thermal characteristics in the tubular hydrothermal exchanger (THE) type after being fitted with baffles. They reported that the thermal performance of a heat exchanger and the reduction of pressure loss are possible by introducing inserts, particularly integrated baffles with circular perforations 32 . studied the role of baffle orientation in modifying the flow structure and heat transfer characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the thermal performance of a heat exchanger and the reduction of pressure loss are possible by introducing inserts, particularly integrated baffles with circular perforations. 32 studied the role of baffle orientation in modifying the flow structure and heat transfer characteristics. The deflectors in the studied model were chosen to be transverse and orientable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many published works about heat transfer and flow mechanisms, which are significant knowledge, for the heat exchangers and engineering devices [1][2][3][4][5][6][7][8][9]. The examples for the heat transfer improvement in various types of the heat exchangers with passive techniques of both numerical and experimental investigations are as follows.…”
Section: Introductionmentioning
confidence: 99%